The problem of 1 Corinthians 11.1-6 and the gender issue in the Corinthian church - Silva, Roberta Alexandrina da (Romanitas - Revista de Estudos Grecolatinos, 2013)
This article examines the issue of gender debates within the Church of Corinth and how Paul of Tarsus, the so-called "Apostle of the Gentiles, build a speech to discuss these issues. Concomitant this, we intend to study the parallel, within the Roman Empire, between behaviors and attitudes regarding the male and female roles.